The effectiveness of neural mobilizations in the treatment of musculoskeletal conditions: a systematic review protocol. (January 2015) - Basson, Annalie; Olivier, Benita; Ellis, Richard; Coppieters, Michel; Stewart, Aimee; Mudzi, Witness
Abstract : Review question/objective : The objective of this review is to identify the effectiveness of neural mobilization techniques in various neuro‐musculoskeletal conditions. Outcomes will be analyzed in terms of subgroups such as low back pain, cervico‐brachial pain and carpal tunnel syndrome. Background : Musculoskeletal disorders were ranked as the second largest contributor to disability worldwide in a study on the global burden of disease.1 Low back pain and neck pain contributed to 70% of disability in this comprehensive population‐based study. Low back pain and neck pain are multifactorial, with heterogeneous populations. It has been proposed that targeting subgroups of patients may result in better treatment outcomes.2, 3 Neck pain associated with upper limb pain is prevalent.4, 5 These patients are more disabled than patients with neck pain alone.4 Similarly, low back pain with leg pain is a common phenomenon and is acknowledged as a predictor for chronicity.6 Neuropathic pain is often associated with musculoskeletal complaints7, 8 including low back pain, 9 whiplash associated disorders (WAD)10, 11 and acute or chronic radiculopathy, and can be a feature of syndromes such as cervico‐brachial pain syndrome.12 According to the International Association for the Study of Pain, neuropathic pain can be described as "pain caused by a lesion or disease of the somatosensory nervous system."13 Leg pain associated with back pain can be caused by central sensitization, denervation, nerve sensitization or somatically referred pain.6 In patients with WAD, neck pain is the most common symptom, but upper limb pain, weakness, paraesthesia and anesthesia are often present.11, 14 Other conditions in which neural tissue is thought to contribute to the clinical picture are, for instance, lateral epicondalalgia15 and carpal tunnel syndrome.16 Management strategies for back pain and neck pain are often multimodal.2, 3 However, the evidence for effective treatment of nerve related pain is lacking.2, 17, 18 Neural mobilizations are often used to affect the neural structures in conditions with signs of neural involvement or neural mechano‐sensitivity.19‐21 Neural mobilizations are defined as interventions aimed at affecting the neural structures or surrounding tissue (interface) directly or indirectly through manual techniques or exercise.22, 23 Neural mobilizations have been studied in various populations such as low back pain, 24 carpal tunnel syndrome, 16 lateral epicondalalgia15 and cervico‐brachial pain.25, 26 Neural mobilization techniques studied include cervical lateral glides for cervico‐brachial pain, 25, 26 nerve gliding exercises for the treatment of carpal tunnel syndrome, 16, 27 cervical lateral glides for lateral epicondalalgia15 and the slump as a neural mobilization technique in the treatment of low back pain.3, 24 No specialized equipment is needed in the performance of neural mobilization techniques, which contributes to its popularity. Neural mobilization is said to affect the axoplasmic flow, 28 movement of the nerve and its connective tissue29 and the circulation of the nerve30 by alteration of the pressure in the nervous system and dispersion of intraneural oedema.30, 31 Neural mobilization decreases the excitability of dorsal horn cells.20 Neural mobilizations can be performed in various ways using passive movement, manual mobilization of the nerve or interface, and exercise. The aim of neural mobilization is to restore the mechanical and neurophysiological function of the nerve.28 Only one systematic review on the effectiveness of neural mobilizations could be identified in the literature.17 Since this review, several more studies have been published on this subject.32‐34 The authors hypothesize that a review of the more recent literature (2008‐2014) may confirm positive support for the use of neural mobilizations for neuro‐musculoskeletal complaints as previously seen by Ellis and Hing.17 This review aims to include a meta‐analysis and subgrouping of conditions which will be an extension of the previous review by Ellis and Hing.17 The outcomes of this systematic review may be used to inform clinical practice and the development of best practice guidelines.